The two-impurity Anderson model: An effective medium approach - Chaves Neto, A. M J; Lagos, Roberto E. [UNESP] (Elsevier, 2002)
The two-impurity Anderson model is solved within a effective medium approach. All impurity parameters are modelled via Slater atomic orbitals. Impurity spectral densities and spin correlation functions are readily computed. Results are presented for the zero temperature, half-filled case. © 2002 Elsevier Science B.V. All rights reserved.
Keywords: Anderson model; Kondo and Anderson lattices; Correlation methods; Crystal atomic structure; Crystal impurities; Electronic density of states; Fermi level; Fermions; Green's function; Hamiltonians; Probability; Atomic orbitals; Crystal lattices